Oral Reading Assessment: Four Conditions Where Caution Is Warranted - Zipoli, R.P.; Ramachandar, S. (Assessment for Effective Intervention, 2023)
Assessments of oral reading are widely used for screening, progress monitoring, and comprehensive evaluations. Despite the utility and technical adequacy of these tools, there are subgroups of students for whom measures of oral reading may be inappropriate. The first section of this article focuses on how tests of oral reading may underestimate word reading ability and reading fluency among four subgroups of students with speech, language, or learning difficulties. These include school-age students who demonstrate word-finding difficulties (which are common among students with a learning disability or developmental language disorder), developmental stuttering, childhood apraxia of speech, and pediatric dysarthria. The second section offers practical recommendations for more accurate assessment procedures, correct placement decisions, relevant professional learning activities, and strategic interdisciplinary teaming. © Hammill Institute on Disabilities 2023.
Keywords: communication disorders; dept.cmd; learning disability; peer-reviewed; reading/literacy